Do acesso clássico à comercialização: especificidades do mercado imobiliário informal na área especial de interesse social de Mãe Luiza, Natal/ RN. - Lima, Huda Andrade Silva de (2012)
This study presents research regarding affordable housing and their effects on the spatial reconfiguration of Natal/ RN, aiming to identify the specificities of the informality of urban land. This study aims to understand how informal housing market operates housing provision for the population located in popular informal settlements, through buying and selling market and rental market of residential properties irregular / illegal. This understanding will be through the neighborhood of Mãe Luisa, Special Area of Social Interest (SASI), located between neighborhoods with a population of high purchasing power and inserted into the tourist shaft of seaside of town. The characterization of informal housing market in Mãe Luiza, from buyers, sellers and renters, will help to understand how these informal transactions operate on SASI and housing provision for public policy development and implementation of housing programs and land regularization for low-income population, adequate to dynamic and reality of housing of informal areas